The Meaning of Pilgrimage at The Grave of Kyai Modjo: A Study of Living Hadis About Grave Pilgrimage - Alibe, Muhammad Tahir; Salim, Arhanuddin; Asma, Andi (Diroyah : Jurnal Studi Ilmu Hadis, 2025)
The tradition of grave pilgrimages has become integral to religious practice in the Indonesian Muslim community. A grave pilgrimage is an order in Islam because it can remind us of death, take lessons, live zuhuds, and encourage us to do better. Grave pilgrimage has become a routine in people's lives, including the grave pilgrimage at Kyai Modjo's grave to honor the services of his struggle against Dutch colonialists. This type of research is a descriptive-analytical qualitative study that aims to describe the meaning of grave pilgrimages for those who make a pilgrimage at the Kyai Modjo Tomb. Using the Hadith Study method, this research focuses on the study of hadith, using the Living Hadith Approach, which aims to understand the perception and meaning of the purpose of the practice of Grave Pilgrimage at the Kyai Modjo Tomb. The data collection involved interviews with academics, cultural experts, and religious leaders. The results of this study indicate that grave pilgrimages are a sunnah of the Prophet. Therefore, the grave pilgrimage tradition is part of the implementation of the arguments of the Qur'an and the Hadith of the Prophet. This research shows the permissibility of performing grave pilgrimages, especially to Ulama, martyrs, and heroes, such as Kyai Modjo in Tondano, North Sulawesi. This research can be a reference, especially about grave pilgrimage with a Living Hadith approach, as well as the grave of Kyai Modjo can be a religious tourism in the future if managed properly.